A cross-jurisdictional evaluation of insurance coverage among HIV care patients following the Affordable Care Act. Issue 4 (3rd April 2017) - Hood, Julia E.; Buskin, Susan E.; Anderson, Bridget J.; Gagner, Alexandra; Kienzle, Jennifer; Maggio, David; Markey, Katie; Reuer, Jennifer; Benbow, Nanette; Wortley, Pascale
ABSTRACT: The impact of the Affordable Care Act (ACA) on HIV care patients, aged 18–64, was evaluated in three jurisdictions with Medicaid expansion (Chicago, New York State, and Washington) and three jurisdictions without Medicaid expansion (Georgia, Texas, and Virginia) using data from the Medical Monitoring Project. Multivariate regression models were used to evaluate insurance status that was reported pre- and post-ACA; self-reported impact of ACA on HIV care was explored with descriptive statistics. The likelihood of having insurance was significantly greater post-ACA compared to pre-ACA in Chicago (aRR = 1.33, 95%CI = 1.20, 1.47), Washington (aRR = 1.15, 95%CI = 1.08, 1.22), and Virginia (aRR = 1.14, 95%CI = 1.00, 1.29). In Washington and Chicago, the likelihood of being Medicaid-insured was greater post-ACA compared to pre-ACA implementation (Chicago: aRR = 1.25, 95%CI = 1.03, 1.53; Washington: aRR = 1.66 95% CI = 1.30, 2.13). No other significant differences were observed. Only a subset of HIV care patients (range: 15–35%) reported a change in insurance that would have coincided with the implementation of ACA; and within this subset, a change in medical care costs was the most commonly noted issue. In conclusion, the influence of ACA on insurance coverage and other factors affecting HIV care likely varies by jurisdiction.